Incorporating q-Rung Picture Fuzzy Frank Prioritized Weighted Aggregators with Multimoora Strategy for Decision Making - Ramesh, Chitra; Kesavan, Prabakaran (Science and Technology Indonesia, 2024)
The Frank norm operators and ˇq-rung picture fuzzy sets offer a versatile framework due to their adjustable parameters. Conversely, prioritized weighted operators are crucial for indicating the relative significance of alternatives and attributes. In this research, we have devised Frank’s prioritized weighted procedure for ˇq-rung picture fuzzy numbers. Thus, the ˇq-rung picture fuzzy prioritized weighted Frank averaging (ˇq-RPFPWFA) and geometric (ˇq-RPFPWFG) operators are presented and analyzed along with some of their properties. Utilizing these proposed operators, a novel approach is established, combining the enhanced MULTIMOORA (MM) procedure with unspecified weight data. A numerical example regarding the multiple attribute group decision making (MAGDM) problem of selecting the financial director of a residential society is handled based upon the aforementioned procedure. Furthermore, we have compared the results with those obtained using available operators. Evidently, the novel ˇq-RPFPWFA and ˇq-RPFPWFG aggregators with the MM technique yield reasonable and consistent outcomes for solving MAGDM.